2019
DOI: 10.1186/s12884-019-2183-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk factors before pregnancy of preterm births in Iran: a population-based case-control study

Abstract: BackgroundPreterm birth is a major cause of prenatal and postnatal mortality particularly in developing countries. This study investigated the maternal risk factors associated with the risk of preterm birth.MethodsA population-based case-control study was conducted in several provinces of Iran on 2463 mothers referred to health care centers. Appropriate descriptive and analytical statistical methods were used to evaluate the association between maternal risk factors and the risk of preterm birth. All tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…The risk of preterm birth in women with a history of stillbirth was higher in the case group comparing with the control group. Soltani et al showed that the risk of preterm birth in women with a history of stillbirth was four times higher than women without it [1]. Malacova et al reported that the risk of preterm birth in women with a history of stillbirth was three to four times higher.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of preterm birth in women with a history of stillbirth was higher in the case group comparing with the control group. Soltani et al showed that the risk of preterm birth in women with a history of stillbirth was four times higher than women without it [1]. Malacova et al reported that the risk of preterm birth in women with a history of stillbirth was three to four times higher.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the association between maternal age and premature birth; both extreme ages either under 18 years or above 40 years are considered to be risk factors for premature birth [24][25][26][27]. Though the majority of the studies concluded that the older maternal age was associated with higher risk of premature birth, Ambrogio and colleagues in their study observed that both extreme ages that is, maternal age under 17 and advanced age over 40 were independent factors for premature birth (OR 2.97; 95%CI 1.24, 7.14 , P<0.005) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Preterm child delivery is de ned as birth before the 37 th week or 259 th day of pregnancy and it has a key factor in mortality and morbidity in infants, children, and even adults [1][2][3]. Based on pregnancy age and according to the World Health Organization (WHO), preterm birth is categorized as highly preterm birth (before 28 th week), very preterm birth (28 th -32 nd week), and moderate and mild preterm birth (32 nd -37 th week) [4].…”
Section: Introductionmentioning
confidence: 99%
“…As shown by different studies, the prevalence of preterm birth in Asia ranges from 7.2% to 13.6% and 5.6% to 34.9% [6,7]. According to WHO (2018) the highest mortality rates of preterm infant (per 100 live births) were in Malawi (18.1), Comoros (16.7%), Kongo Preterm birth is a multi-cause event and it is related to genetic, environment, and immunology factors [1,9]. The main causes of preterm birth in the developing countries are infectious diseases and lack of access to health cares.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation